Monitoring stem cell differentiation using Raman microspectroscopy: chondrogenic differentiation, towards cartilage formation. Issue 1 (6th November 2020) - Ravera, Francesca; Efeoglu, Esen; Byrne, Hugh J.
Abstract : Raman microspectroscopy is employed to monitor the differentiation of mesenchymal stem cells to chondrocytes, from subcellular to extracellular matrix evolution. Abstract : Mesenchymal Stem Cells (MSCs) have the ability to differentiate into chondrocytes, the only cellular components of cartilage and are therefore ideal candidates for cartilage and tissue repair technologies. Chondrocytes are surrounded by cartilage-like extracellular matrix (ECM), a complex network rich in glycosaminoglycans, proteoglycans, and collagen, which, together with a multitude of intracellular signalling molecules, trigger the chondrogenesis and allow the chondroprogenitor to acquire the spherical morphology of the chondrocytes. However, although the mechanisms of the differentiation of MSCs have been extensively explored, it has been difficult to provide a holistic picture of the process, in situ . Raman Micro Spectroscopy (RMS) has been demonstrated to be a powerful analytical tool, which provides detailed label free biochemical fingerprint information in a non-invasive way, for analysis of cells, tissues and body fluids. In this work, RMS is explored to monitor the process of Mesenchymal Stem Cell (MSC) differentiation into chondrocytes in vitro, providing a holistic molecular picture of cellular events governing the differentiation. Spectral signatures of the subcellular compartments, nucleolus, nucleus and cytoplasm were initially probed and characteristic molecular changes between differentiated and undifferentiated were identified. Moreover, high density cell micromasses were cultured over a period of three weeks, and a systematic monitoring of cellular molecular components and the progress of the ECM formation, associated with the chondrogenic differentiation, was performed. This study shows the potential applicability of RMS as a powerful tool to monitor and better understand the differentiation pathways and process.